Hidroponik Hidroponik Sistem Rakit Apung Solusi Urban Farming di Kota Surakarta - Saputro, Avisema Sigit; Sumarmi, Sumarmi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: The Urban farming training activity on the Floating Raft Hydroponic System was carried out in Pundung Gede RT 06 RW 09, Joglo Village, Banjarsari Banjarsari District, Surakarta on August 17 2024. The problem is that Pundung Gede residents are not yet familiar with floating raft hydroponics. All 15 participants were PKK mothers. The characteristics of Joglo village are almost the same as those of other urban areas, namely the lack of land for cultivating plants. This activity aims to provide insight to residents about urban agriculture so that the remaining land in urban areas can still be cultivated for cultivation using a floating raft hydroponic system. Methods: The methods used in this activity are counseling, training, and mentoring. Apart from that, the expected output is a change in the behavior of residents, especially in Joglo village, in managing the limited land for cultivating vegetables so that it can reduce daily vegetable shopping expenses for households. Results: Showed that a large number of participants understood hydroponics. Conclusion: the activity shows that the women of Joglo village could practice floating raft cultivation in their respective homes.